EVALUATION OF WATER QUALITY MANAGEMENT IN ORGANIC FERTILIZER INDUSTRY: A CASE STUDY AT PT BIO MARAJA NUSANTARA MAKASSAR - Christopaul Pala'langan Toding Layuk; Muh. Fikruddin Buraerah; Nur Isra (Purifikasi, 2025)
Management of water quality generated from the wastewater effluent of PT Bio Maraja Nusantara, a company that produces organic fertilizers in Makassar.. This fertilizer production activity produces liquid waste that has the potential to pollute the environment, especially local water quality. This study evaluates water quality based on Government Regulation No. 22 of 2021 concerning liquid waste management. Water quality testing measured physical, chemical, metal, and microbiological parameters. The results showed that the water quality met the quality standards set by the regulation, with the tested water not contaminated by hazardous materials such as odor, color, heavy metals, or pathogenic microorganisms. Analytical results showed the water had undetectable odor and color, low Total Dissolved Solids (TDS) content, and turbidity below the quality limit. In addition, the pH value, nitrate, nitrite, and hexavalent chrome content were also within safe limits. Microbiological testing showed the water was free from E. coli and coliform contamination. This study shows that effluent management efforts at PT Bio Maraja Nusantara effectively minimize negative impacts on local water quality and contribute to industrial water quality management literature in the sustainable agriculture sector.